J. Gibson's theory of direct perception - Martišius , V. (Psichologija, 1985)
The principal aim of the present paper is to evaluate J. Gibson's contribution to the comprehension of visual perception. It is concluded that some definitions or the concepts and principles of the ecological approach are self-contradictory and unessential. The theory of direct perception doesn't allow many important experimental findings to be explained. It is because of the limitations in J. Gibson's theory that the latter can't be considered a significant alternative to the theories in which emphasis is placed on the importance of internal representation for perceptual processes.
Keywords: direct perception